An Analysis Of Students’ Experience in Online English Class at SMAN 1 Mandah Academic Year 2020/2021 - Shafikri AS, Agung; Reflinda, Reflinda; Melani, Meylann; Eliza, Eliza (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Various kinds of new things and problems were experienced by the students during learning English in the online class, among the things were students’ felt difficult understanding the material given by the teacher, the lack of students’ motivation in learning English, and the lack of students’ interesting of learning English. Thegoal of this research is to find out how students experience online English classes during the covid-19 pandemic. This research used a descriptive quantitative method. The population in this research were 11thgrade students at SMAN 1 Mandah. The sample in this research was two classes of 11th-grade students at SMAN 1 Mandah, there are XI IPA 3 and XI IPS 1 as many as 54 students. The data collection used apurposive sampling technique because the sample in this study was taken randomly with certain characteristics, there are the students who feel learning English in the online class. The data collection was in the form of a questionnaire. This research found that in general, the results of the research on students’ experience in online English classes or distance learning were categorized as enough because 19 of 20 statements that given to the students were showed the results with enough categories, and only 1 of the statement that reached the level with a good category. Therefore, the researcher can conclude that the results of this research on students’ experience in online English classes are only limited to enough levels and have not reached a good level with a percentage of 68,5%. Based on the results of the data analysis seen from the Likert Scale that showed students’ experience in online English classes, which can be concluded that the average results of the questionnaire given to the students in students’ experience in online English class were declared enough because it has not yet reached a good level of students’ experience in online English class.